The burden of maternal morbidity and mortality attributable to hypertensive disorders in pregnancy: a prospective cohort study from Uganda - Nakimuli, Annettee; Nakubulwa, Sarah; Kakaire, Othman; Osinde, Michael O.; Mbalinda, Scovia N.; Kakande, Nelson; Nabirye, Rose C.; Kaye, Dan K. (BMC pregnancy and childbirth, 2016)
Hypertensive disorders of pregnancy are a major cause of morbidity and mortality. The objective was to estimate the disease burden attributable to hypertensive disorders of pregnancy in two referral hospitals in Uganda. Methods: Through a prospective cohort study conducted in Jinja and Mulago hospitals in Uganda from March 1, 2013 and February 28, 2014, hypertension-related cases were analyzed. Maternal near miss cases were defined according to the WHO criteria. Maternal deaths were also analyzed. The maternal near miss incidence ratio, the case-specific severe maternal outcome ratio, the case-specific maternal mortality ratio and the case-fatality ratio were computed. Results: Of 403 women with hypertensive disorders of pregnancy, 218 (54.1 %) had severe preeclampsia, 172 (42.7 %) had eclampsia, and 13 had chronic hypertension or Hemolysis, elevated liver enzymes or low platelets (HELLP) syndrome. The case-specific maternal near miss incidence ratios was 8.60 per 1,000 live births for all hypertensive disorders, 3.06 per 1,000 live births for severe preeclampsia and 5.11 per 1,000 live births for eclampsia. The casespecific severe maternal outcome ratio was 9.37 per 1,000 live births for all hypertensive disorders, and was 3.25 per 1,000 live births for severe preeclampsia and 5.61 per 1,000 live births for eclampsia. The case-specific maternal mortality ratio was 780 per 100,000 live births for all hypertensive disorders, and was 1940 per 100,000 live births for severe preeclampsia and 501 per 100,000 live births for eclampsia. The case-fatality ratio was 5.1 % overall (for all hypertensive disorders), but was 8 times higher for eclampsia compared to severe preeclampsia. Cyanosis, abnormal respiration, oliguria, circulatory collapse, coagulopathy, thrombocytopenia, and elevated serum lactate were significantly associated with severe maternal outcomes. Conclusion: There is high morbidity attributable to hypertensive disorders in pregnancy. Since some of the complications associated with morbidity can be recognized early, it is possible to prevent severe morbidity through early intervention with delivery, antihypertensive therapy and prophylactic magnesium sulphate treatment. The findings highlight the feasibility of implementing a facility-based surveillance system for severe maternal morbidity due to hypertensive disorders.
Keywords: maternal morbidity; mortality attributable; disorders